(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
Philology, the study of language in written historical sources, remains a fundamental discipline for understanding human culture, history, and communication. Its long-standing tradition has provided invaluable insights into ancient civilizations, literature, and linguistic development. However, in the contemporary world, philology faces a range of urgent and complex challenges that threaten its relevance and efficacy. These challenges arise due to rapid technological progress, globalization, shifting linguistic landscapes, evolving academic priorities, and disparities in access to resources. This article explores the key issues currently confronting philology and discusses potential pathways for its preservation and growth.